From the internal structure to the librations of satellites and back - Mendonça, Yeva Gevorgyan de (2020)
In this thesis we study simple effective rheological models to describe forced librations and dissipative phenomena in dynamical astronomy. We address the direct implementation of the Andrade rheology in the time domain to model the internal structure of celestial bodies. The approach allows for large eccentricities and non-periodic perturbations of the orbit. Furthermore, Maxwell and Andrade effective rheologies are compared and some connections between the observed librations of celestial bodies and their internal structure are established. The relevance of the contribution of the forced librations to the dissipation rate of the celestial objects is verified. The influence of the permanent deformations, represented by the so-called prestress, on the librations of celestial bodies is also studied. We make some first attempts to model multi-layered rheologies and to compare them with effective rheological models. The models are validated by means of concrete applications: the analysis of the forced librations of Enceladus, the Moon, and Mercury. Our results indicate the importance of multi-layered rheologies in some cases.